Teaching Portuguese pronunciation to Spanish speakers - Soares, Cristiane (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
Researchers interested in the acquisition of Portuguese as a second language or as a foreign language have discussed the advantages and disadvantages faced by Spanish speakers when learning Portuguese. The positive transfer of lexical and grammatical features common to both languages is, without doubt, among the advantages encountered by these leaners. However, it is undeniable that the negative interference of Spanish phonological patterns can bring great challenges to the development of a proper pronunciation in Portuguese. Researches in this field have highlighted the need to develop activities that most effectively develop pronunciation among these learners. The present study aims to review major studies devoted to such discussion and to present oral activities that have proven to be effective in the development of pronunciation and communication amongSpanish speakers learning Portuguese.
Keywords: Pronunciation; Oral activities; Portuguese for Spanish speakers